EDUKASI MERAWAT DIRI DAN CINTAI DIRI PADA SISWA SD NEGERI I PULO PANJANG KECAMATAN PULO AMPEL KABUPATEN SERANG - setiawati, rini (Universitas Islam Sumatear Utara, 2025)
Personal hygiene is a fundamental aspect of health maintenance, particularly among elementary school-aged children who are in a critical stage of development. Body parts such as hands, nails, hair, face, eyes, ears, nose, and mouth play essential biological and social functions and therefore require consistent hygiene practices. Poor hand and nail hygiene may serve as a breeding ground for pathogens, while unkempt hair can lead to decreased self-esteem due to aesthetic concerns. Proper facial and eye cleaning, along with ear and nasal hygiene, are necessary to prevent infections. Meanwhile, oral and dental care plays a crucial role in digestion and overall health. Educating children about comprehensive body care from an early age is a preventive strategy to cultivate long-term clean and healthy living habits. This article highlights the importance of self-care practices as a concrete form of clean behavior application among elementary school students.